EFFECTS OF LEARNING BASED ON REALISTIC MATHEMATICS EDUCATION TO MATHEMATICAL CONNECTION ABILITY AND ATTITUDE TOWARDS MATHEMATICS OF PRATHOMSUKSA FIVE STUDENTS - Suntronnun, Siraprapa; Sumirattana, Sunisa (Journal of MCU Nakhondhat, 2023)
The purposes of this research are as follows: (1) to compare the mathematical connection ability of students before and after learning; (2) to compare the mathematical connection ability of students after learning with a 70% criterion; and (3) to compare the attitudes of students toward mathematics before and after learning. The subjects of this study were 33 Grade Five students at Watboth School in Singburi. They were randomly selected using cluster random sampling. The experiment lasted for 14 periods. The instruments used in this research were Realistic Mathematics Education lesson plans, the mathematical connection ability test and the attitude towards mathematics test. The tools use in this study include a t - test for Dependent Samples and a t - test for One Sample were employed in analyzing the data. The findings were as follows: (1) the mathematical connection ability of students in the experimental group after learning was statistically higher than before learning with a .05 level of significance; (2) the mathematical connection ability of students in the experimental group after learning was statistically higher than the 70% criterion with a .05 level of significance; and (3) attitudes toward mathematics among students in the experimental group after learning was statistically higher than before learning at the .05 level of significance.